Welsh productivity performance: Lost cause or still waiting for a miracle? - Andrew Henley (Welsh Economic Review (WER), 2024)
Wales has a chronic and severe problem of low productivity, and shares with the wider UK two decades of stagnant productivity. Significantly, Wales has a severe and persistent productivity gap with other UK nations and regions, and with other international competitors. The aim of this paper is to give an overview of the issues together with some analysis of both the Welsh productivity gap and the intra-Wales dispersion of productivity. The paper describes potential macro and micro productivity drivers and argues that there is an urgent need to (re-) promote productivity within Wales as a policy objective.
Keywords: 330